Sistim Tampilan Jadwal Pesawat Udara Dengan Mode Dual Display Di Bandara Ahmad Yani Semarang - Suseno, Hari (JSINBIS (Jurnal Sistem Informasi Bisnis), 2012)
Schedule for airline passengers is important information that is provided by the airport manager. Airport flight information on the display screen using a media schedule called flight information display system (FIDS). FIDS system comes from two processes that display arrival and departure information. The device comes from the appearance of two separate computer with information for each. The use of two computers that are used to the old system at the airport FIDS devices. This research aims to create an integrated FIDS system device to combine the information into one unified display in dual display mode pattern display (dual view). Design systems using software programming VB6 and hardware modifications applied to design a system FIDS new on view flight schedules. With a centralized system obtained an interactive display schedules for flight schedule. Keywords : FIDS system; Flight schedule; DisplayÂ  information